Oval - Wilk, Elvia 1989- (Soft Skull, 2019)
"In the near future, Berlin's real estate is being flipped in the name of "sustainability," only to make the city even more unaffordable; artists are employed by corporations as consultants; and the weather is acting strange. In search of affordable housing, young couple Anja and Louis move into a community on an artificial mountain, The Berg--yet another "eco-friendly" initiative run by a corporation called Finster. They're offered a home rent-free in exchange for keeping quiet about the seriously malfunctioning infrastructure of the experimental house. But when Louis returns home from his mother's funeral in America, Anja is convinced he has changed. He seems to be in denial of his grief and newly idealistic, consumed by a secret project at the NGO where he works as an artist-consultant. Anja is horrified when she discovers what Louis has invented: a pill called Oval that temporarily rewires the user's brain to be more generous. Louis is convinced that if he can introduce the drug into the Berlin club scene, he can finally remedy the income disparity that has made Berlin so unlivable. Oval is a fascinating portrait of the unbalanced relationships that shape our world, as well as a prescient warning of what the future may hold"--
Keywords: Man-woman relationships / Fiction; Berlin (Germany) / Fiction; FICTION / General; Man-woman relationships; Germany / Berlin; Science fiction; Dystopias; Fiction